2004
DOI: 10.1080/00268970410001703903
|View full text |Cite
|
Sign up to set email alerts
|

Methanol coupling in the zeolite chabazite studied via Car–Parrinello molecular dynamics

Abstract: We have used Car-Parrinello constrained molecular dynamics to study the coupling of two molecules of methanol in the zeolite chabazite to form ethanol and water. We have chosen to study this reaction because it represents the formation of the first C-C bond, which is thought to be the rate limiting step for the MTO and MTG processes. We have elucidated a new mechanism for this reaction that does not require the prior formation of surface methoxy groups or dimethyl ether intermediates. The mechanism involves st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 27 publications
(25 reference statements)
3
15
0
2
Order By: Relevance
“…[36,56] Die Erklärung von Espinoza, [96] dass eine kritische Menge DME bençtigt wird, um die Reaktion am Laufen zu halten, kann ausgeschlossen werden, da die gemessenen Methanol-und DME-Konzentrationen in Abbildung 11 zeigen, dass ein Methanol/DME-Gleichgewicht schon bei kurzen Verweilzeiten hergestellt wird und somit die kritische Menge an DME zu jeder Zeit vorhanden sein muss. [99] Gleichwohl der Vielzahl an vorgeschlagenen Mechanismen ist der Reaktionsweg über den Kohlenwasserstoffpool heute allgemein akzeptiert und liefert den wohl wichtigsten Beitrag für die Umwandlung von Methanol an Zeolithen. Viele andere Mechanismen wurden für die Bildung von Kohlenwasserstoffen aus Methanol vorgeschlagen.…”
Section: Kinetik Und Autokatalyseunclassified
“…[36,56] Die Erklärung von Espinoza, [96] dass eine kritische Menge DME bençtigt wird, um die Reaktion am Laufen zu halten, kann ausgeschlossen werden, da die gemessenen Methanol-und DME-Konzentrationen in Abbildung 11 zeigen, dass ein Methanol/DME-Gleichgewicht schon bei kurzen Verweilzeiten hergestellt wird und somit die kritische Menge an DME zu jeder Zeit vorhanden sein muss. [99] Gleichwohl der Vielzahl an vorgeschlagenen Mechanismen ist der Reaktionsweg über den Kohlenwasserstoffpool heute allgemein akzeptiert und liefert den wohl wichtigsten Beitrag für die Umwandlung von Methanol an Zeolithen. Viele andere Mechanismen wurden für die Bildung von Kohlenwasserstoffen aus Methanol vorgeschlagen.…”
Section: Kinetik Und Autokatalyseunclassified
“…TPS efficiently calculates rates and reactive trajectories by focusing on rare reactive trajectories. 27 Each shooting point from TPS provides information about the reaction coordinate: where the trajectory was initiated and whether each end committed to the product state. TPS and related path sampling algorithms [14][15][16] have been used to study ice nucleation, 17,18 DNA transcription, 19 DNA hybridization, 20 Grotthus proton transfer, 21 protein folding, [22][23][24] methionine oxidation, 25 transfer of molecules across lipid bilayers, 26 the phage-switch, 16 and heterogeneous catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…These results correspond with earlier findings from theoretical studies applying static and dynamical approaches, stating that two methanol molecules are able to deprotonate the BAS in zeolitic catalysts. 49,[118][119][120][121][122] Even if an additional methanol molecule is present, the lower acid strength of H-SAPO-5 as compared to H-SSZ-24 is still reflected in the relatively low probabilities to protonate methanol. A convergence check of the calculated probabilities confirmed that the 50 ps MD simulations give sufficient sampling to obtain reliable results concerning co-adsorption behavior (see Fig.…”
mentioning
confidence: 99%